Taxonomic review of Syzeuxis Hampson, 1895, with a discussion of biogeographical aspects (Lepidoptera, Geometridae, Larentiinae) - Li, Jing; Xue, Dayong; Han, Hongxiang; Galsworthy, Anthony C. (Zootaxa, 2012)
The genus Syzeuxis Hampson, 1895 is reviewed. In addition to the 11 species known worldwide, two new species aredescribed: S. furcalineas sp. nov. from Assam, India and S. pavonata sp. nov. from Yunnan, China. One new synonymy isgiven: S. miniocalaria Xue, 1999 is sunk in S. heteromeces Prout, 1926. All the known species are redescribed and lectotypesare designated for S. magnidica Prout, S. subfasciaria (Wehrli) and S. nigrinotata (Warren). Generic characters based on allspecies are summarized. Illustrations of moths and genitalia are presented. The tribal placement of the genus is discussed, withthe conclusion that it should be placed in the tribe Trichopterygini. A pilot phylogenetic study based on morphological charac-ters of Syzeuxis indicates that four species-groups can be identified. The biogeographical aspects of the genus are also discussed.